2023
DOI: 10.1002/kin.21640
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase kinetics, POCPs, and an investigation of the contributions of VOCs to urban ozone production in the UK

Abstract: Ambient concentrations of 22 volatile organic compounds (VOCs) measured at London Marylebone Road (LMR), an urban traffic site, and London Eltham (LE), an urban background site, were analyzed over a period of 23 years to assess the impact of pollution control strategies. A significant decrease in ambient concentration is seen for the majority of VOCs analyzed with total VOC burden decreasing by 76% and 59% for LMR and LE, respectively, across the period studied. This is likely as a result of legislative contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although alkanes are often emitted from ozone production analyses, due to their comparatively low reactivity as VOCs, they have recently been shown to play a substantial role in tropospheric ozone formation. At the monitoring stations of both London Eltham (LE) and London Marylebone Road (LMR), alkanes accounted for 60% (3 out of 5) of the greatest contributors to ozone production, along with ethene and propene [25]. A study at LMR also suggested the importance of certain alkanes, demonstrating that approximately 75% of the total ozone formation potential (OFP) at this site was accounted for by ethene, propene, m + p-xylene, toluene, isopentane, n-butane, o-xylene and iso-butane [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although alkanes are often emitted from ozone production analyses, due to their comparatively low reactivity as VOCs, they have recently been shown to play a substantial role in tropospheric ozone formation. At the monitoring stations of both London Eltham (LE) and London Marylebone Road (LMR), alkanes accounted for 60% (3 out of 5) of the greatest contributors to ozone production, along with ethene and propene [25]. A study at LMR also suggested the importance of certain alkanes, demonstrating that approximately 75% of the total ozone formation potential (OFP) at this site was accounted for by ethene, propene, m + p-xylene, toluene, isopentane, n-butane, o-xylene and iso-butane [5].…”
Section: Methodsmentioning
confidence: 99%
“…NO x emission reductions alone are, therefore, not an effective solution for universally reducing pollution levels. Reductions of NO and NO 2 are still important to reduce NO x pollution itself but, at VOC-limited sites, it is more important to reduce emissions of the key VOCs contributing to ozone formation, such as ethene, propene, m + p-xylene, toluene, isopentane, n-butane, o-xylene and iso-butane [5,25,48]. This avoids escalating levels of harmful tropospheric O 3 , which not only has negative health impacts but also contributes to global warming.…”
Section: Oxidant (Ox) Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the continuous development of civilization, increasingly serious environmental degradation problems lead human society into an unprecedented predicament. , Volatile organic compounds (VOCs) are one of the major components of air pollutants and are mainly derived from the combustion of fossil fuels and emissions of vehicles. Propane (C 3 H 8 ), as a short-chain hydrocarbon, is one of the precursors to near-ground ozone (O 3 ), energetically deteriorating both the ecosystem and human health. In this context, there is an ongoing requirement for the abatement of C 3 H 8 to contribute to environmental sustainability. Compared with other VOC elimination technologies, catalytic oxidation has aroused a tremendous amount of attention due to its incomparable efficiency at relatively low operating temperatures and eco-friendliness. , The most commonly utilized catalysts in catalytic oxidation are supported noble-mental-based materials. By far, Pt-based catalysts are one of the most widespread materials and have been studied profoundly because they can satisfy the requirements for VOC elimination at low temperatures. , …”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the UK published Air Quality Standards Regulations (AQSR) which prompted national PM 2.5 reduction measures, including a specific annual average concentration aim to be met by 2020 [21]. In UK urban areas, the yearly average PM 2.5 concentrations are decreasing over time due to pollution control strategies [22] and ground-level O 3 concentrations were reported to have been increasing over the preceding decade [23][24][25]. However, the current levels of PM 2.5 in urban sites still exceed legislation.…”
Section: Introductionmentioning
confidence: 99%